Improving The Ability To Understand Reading Contents Through Cooperative Team Type Assisted Learning In Class X Students Of Al-Amien Bugih High School Students - Fredy Yunanto (LP2M IAI Nazhatut Thullab Sampang, 2019)
Abstract: Team Assisted Individualization learning method is elaboration learning that is proven effective in helping students memorize reading information. The purpose of this study was: to find out student learning activities, student responses, and improve skills in understanding the contents of the. The research method used was observation, questionnaire, and denag test. The type of research was class X research of Al-Amien Bugih High School students with 20 students. The researcher used the observation method to find out student learning activities, questionnaires to determine student responses, and test methods to find out the skills to understand the contents of the reading. Analysis of the data using descriptive data analysis. From the results of data analysis, it can be concluded that student learning activities have increased from cycle 1 to good category (2.7) to very good category (3.61) in cycle 2, student responses to improvement from cycle 1 are categorized as negative (50.6) to be positive (70.6) in cycle 2, and reading comprehension skills improved from cycle 1 to less (50) to be sufficient (70) in cycle 2. Keywords: Team Assisted Individualization, Understanding Reading Contents. Abstrak: Metode pembelajaran Individual Assisted Individualization adalah pembelajaran elaborasi yang terbukti efektif dalam membantu siswa menghafal informasi membaca. Tujuan dari penelitian ini adalah: untuk mengetahui kegiatan belajar siswa, respon siswa, dan meningkatkan keterampilan dalam memahami isi bacaan. Metode penelitian yang digunakan adalah observasi, angket, dan tes denag. Jenis penelitian adalah penelitian kelas X siswa SMA Al-Amien Bugih dengan 20 siswa. Peneliti menggunakan metode observasi untuk mengetahui kegiatan belajar siswa, angket untuk menentukan respon siswa, dan metode tes untuk mengetahui keterampilan memahami isi bacaan. Analisis data menggunakan analisis data deskriptif. Dari hasil analisis data, dapat disimpulkan bahwa aktivitas belajar siswa mengalami peningkatan dari siklus 1 ke kategori baik (2,7) menjadi kategori sangat baik (3,61) pada siklus 2, respons siswa terhadap peningkatan dari siklus 1 dikategorikan negatif (50,6). ) menjadi positif (70,6) pada siklus 2, dan keterampilan membaca pemahaman meningkat dari siklus 1 menjadi kurang (50) menjadi cukup (70) pada siklus 2. Kata kunci: Team Assisted Individualization, Memahami Konten Membaca.